Maritime engineering and technology : proceedings of MARTECH 2011, 1st International Conference on Maritime Technology and Engineering, Lisbon, Portugal, 10-12 May 2011 /: proceedings of MARTECH 2011, 1st International Conference on Maritime Technology and Engineering, Lisbon, Portugal, 10-12 May 2011. (©2012) - Unknown
No abstract available